Comparative effects of lifelong moderate-intensity continuous training and high-intensity interval training on blood lipid levels and mental well-being in naturally ageing mice - Ling Yang; Wentao Lin; Xu Yan; Zhishang Zhang (Experimental Gerontology, 2024)
Objective: This study aimed to investigate the impact of lifelong exercise, including both moderate-intensity continuous training and high-intensity interval training, on blood lipid levels and mental behaviour in naturally ageing mice to identify effective exercise strategies for ageing-related health issues. Methods: Six-week-old male BALB/c mice were randomly assigned to one of four groups: young control (YC), natural ageing control (OC), lifelong moderate-intensity continuous exercise (EM), and lifelong high-intensity interval exercise (EH) groups. The EM group was trained at a speed corresponding to 70 % of the maximum running speed, while the EH group was trained at a running speed alternating between 50 % of the maximum running speed, 70 % of the maximum running speed, and 90 % of the maximum running speed. All exercise sessions were conducted three times per week, with each session lasting 50 min. Behavioural tests and blood sample collection were conducted at 72 weeks of age. Results: Ageing in mice led to changes in muscle and fat mass. Both the EM and EH groups showed greater muscle mass and lower fat mass than did the OC group. Ageing was associated with elevated anxiety (fewer open arm entries, time spent in the central region) and depression (lower sucrose preference) indicators. However, these changes were reversed in both exercise groups, with no differences between the two exercise groups. Blood lipid levels, including total cholesterol (TC), total triglycerides (TGs), low-density lipoprotein (LDL), and free fatty acid (FFA) levels, were greater in the OC group than in the YC group. Additionally, the OC group exhibited lower high-density lipoprotein (HDL) levels. However, both the EM and EH groups exhibited improved lipid profiles compared to those of the YC group. Conclusion: Lifelong exercise, whether moderate-intensity continuous or high-intensity interval training, can preserve body health during ageing, prevent anxiety and depression, and maintain stable blood lipid levels. Both exercise types are equally effective, suggesting that exercise intensity may not be the critical factor underlying these beneficial adaptations.